Students' Attitudes Towards Cooperative Learning in Offline and Online Language Classroom - Harianto, Muhammad Bayu Aji Putra; Suharyadi, Suharyadi; Tresnadewi, Shinta (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
This study aimed to seek the students of English as a Foreign Language (EFL) views regarding their experiences on group work (GW) in online and offline settings. The findings showed that the majority of the students who experienced online and offline GW have positive perception. Utilizing a CL strategy may benefit students in increasing self-confidence and motivation, student-centered environment, and taking responsibility. Regardless of the benefits, the students who perceived GW negatively were in online settings due to internet connection issues, less GW experience, and unfamiliar with the application and software. Therefore, this study benefits students, academicians, and policymakers.